Regulation of mRNA stability by RBPs and noncoding RNAs contributing to the pathogenicity of Th17 cells. Issue 5 (4th May 2021) - Zhang, Yiwei; Wei, Zhiyuan; Dong, Hui; Zhou, Jian; Yuan, Jizhao; Ni, Bing; Wu, Yuzhang; Han, Chao; Tian, Yi
ABSTRACT: Th17 cells remain one of the most important subsets of T cells in numerous autoimmune and chronic inflammatory diseases. Posttranscriptional regulation (PTR), especially mRNA stability, has recently emerged as an important mechanism that controls the fate of Th17 cells. This review summarizes the current knowledge on RNA-binding proteins (RBPs), microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) that induce mRNA stability changes and their roles in mediating the differentiation, proliferation, function, and migration of Th17 cells. In addition, we summarize the role of RNA modifications and nonsense-mediated mRNA decay (NMD) in Th17 cells. Ongoing research will help to identify practical applications for the regulation of mRNA stability and provide potential targets to prevent and treat Th17-related autoimmune diseases.